Research progress on the association of ultraviolet radiation with endocrine system and hormone levels - Liangzi LIANG; Lu TANG; Jiande HAN; Naiyu LIN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
The skin serves as the body's primary defense against external insults. Ultraviolet lights from the sun can directly impact the skin surface, affecting internal environment. At the same time, the body's response to ultraviolet lights varies with hormone levels. Under different levels of sex hormone, ultraviolet light can modulate local glucocorticoid levels, resulting in inhibition of inflammation, immunosuppression, and regulation of insulin-related glucose and lipid metabolism. In contrast, melatonin can inhibit ultraviolet irradiation-induced skin aging. This article explores the links between ultraviolet irradiation and corticoids, sex hormones, insulin, and melatonin, facilitating the development of approaches for the prevention and treatment of diseases.